2018
DOI: 10.4149/km_2018_5_325
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Al-4.5%Cu alloy with the addition of silicon carbide and bamboo leaf ash

Abstract: The stir-casting method was employed to study the effect of adding silicon carbide and the bamboo leaf ash into the Al-4.5wt.%Cu alloy. The standard procedure was followed in analysing the mechanical behaviour of the fabricated composites on parameters such as density, tensile strength, and hardness. Optical microscope, scanning electron microscope with energy dispersive analysis of X-rays, and X-ray diffraction analysis helped in studying the microstructure of the composites. The study reveals that the reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(46 reference statements)
1
0
0
Order By: Relevance
“…As the copper nanoparticles increases from 1wt% to 4wt %, the hardness values increases [24], this can be attributed to low porosity obtained as the copper nanoparticles concentration increases and strain fields created around the particulates which impede the motion of dislocation, thereby causing increase in hardness values [2]. Similar results were observed by Kumar and Birru (2018) [25] who investigated the characterization of Al-4.5%Cu alloy with the addition of silicon carbide and bamboo leaf ash, and exhibited higher hardness value as reinforcements increases. This is also in agreement with Mittal and Muni (2013) [26] who investigated the fabrication and characterization of mechanical properties of Al-RHA-Cu hybrid metal matrix composites and concluded that addition copper further increase hardness.…”
Section: Hardnesssupporting
confidence: 56%
“…As the copper nanoparticles increases from 1wt% to 4wt %, the hardness values increases [24], this can be attributed to low porosity obtained as the copper nanoparticles concentration increases and strain fields created around the particulates which impede the motion of dislocation, thereby causing increase in hardness values [2]. Similar results were observed by Kumar and Birru (2018) [25] who investigated the characterization of Al-4.5%Cu alloy with the addition of silicon carbide and bamboo leaf ash, and exhibited higher hardness value as reinforcements increases. This is also in agreement with Mittal and Muni (2013) [26] who investigated the fabrication and characterization of mechanical properties of Al-RHA-Cu hybrid metal matrix composites and concluded that addition copper further increase hardness.…”
Section: Hardnesssupporting
confidence: 56%